2020
DOI: 10.3390/applmech1010005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Load-Bearing Capacity of Composite Parts with Low-Velocity Impact Damage: Identification of Intra- and Inter-Ply Constitutive Models

Abstract: Assessments of residual load-carrying capacity are often conducted for composite structural components that have received impact damage. The availability of a verified simulation methodology can provide significant cost savings when such assessments are required. To support the development of a reliable and accurate simulation methodology, this study investigated the predictive capabilities of a stacked solid-shell finite element model of a cylindrical composite component with a damage mechanics-based descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The three exploration holes reveal that the thickness of the sludge layer is about 10 m and the filling layer is about 4–6 m. Three test areas are arranged in this test, and three test piers are arranged in each test area. The three test piers in test area 1 are 1-1, 1-2, and 1-3; the three test piers in test area 2 are 2-1, 2-2 and 2-3; The three test piers in test area 3 are 3-1, 3-2 and 3-3 [ 13 ]. See Table 2 for test pier parameters.…”
Section: Field Bearing Capacity Model Test Of Special Water Conservan...mentioning
confidence: 99%
See 1 more Smart Citation
“…The three exploration holes reveal that the thickness of the sludge layer is about 10 m and the filling layer is about 4–6 m. Three test areas are arranged in this test, and three test piers are arranged in each test area. The three test piers in test area 1 are 1-1, 1-2, and 1-3; the three test piers in test area 2 are 2-1, 2-2 and 2-3; The three test piers in test area 3 are 3-1, 3-2 and 3-3 [ 13 ]. See Table 2 for test pier parameters.…”
Section: Field Bearing Capacity Model Test Of Special Water Conservan...mentioning
confidence: 99%
“…e three test piers in test area 1 are 1-1, 1-2, and 1-3; the three test piers in test area 2 are 2-1, 2-2 and 2-3; e three test piers in test area 3 are 3-1, 3-2 and 3-3 [13]. See Table 2 for test pier parameters.…”
Section: Project Overview and Selection Of Test Areamentioning
confidence: 99%
“…Aleksandr Cherniaev et al, used the tiebreak contact algorithm to model interlaminar damage behavior and analyzed the effect of nonphysical parameters of the interlaminar material model on the prediction of compressive damage loads in damaged composite cylinders. The peak stress parameter NLFS of the interlaminar model was able to accurately predict the damage loads observed in physical experiments when the parameter SLIMC, associated with the continuous damage criterion, was between 0.6 and 1 [ 10 ]. Jinyang Zheng et al, used the tiebreak contact algorithm to simulate interlaminar failure behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, similarly to conventional unidirectional tape-and woven fabric-based materials (see, e.g., [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]), in-service damage, such as tool dropping or unintended collision, can be a cause for severe reduction in load-carrying capacity of NCF composites [20][21][22][23][24][25]. For example, Bibo et al [24] demonstrated that resistance to propagation of damage and the compression after impact strength of NCF panels were not superior to their unidirectional prepreg tape equivalents.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, two LS-DYNA material models were evaluated: *MAT_ENHANCED_COMPOSI TE_DAMAGE (MAT 54) and *MAT_LAMINATED_COMPOSITE_FABRIC (MAT 58). Both constitutive models have been widely used for modeling of variety of in-service damage scenarios in UD tape and woven fabric composites, including damage induced by axial crushing (MAT 54: [5,12,[33][34][35][36]; MAT 58: [12,[37][38][39][40][41][42]) and transverse loading (MAT 54: [36,43,44]; MAT 58: [6,[45][46][47]). The main takeaway from these studies is that both constitutive models can quite accurately predict the behavior of tape and woven fabric materials but require determination of their non-physical parameters (so-called stress limit factors, element erosion strain, etc.)…”
Section: Introductionmentioning
confidence: 99%